2011
DOI: 10.1088/0022-3727/44/16/165302
|View full text |Cite
|
Sign up to set email alerts
|

Effect of lubricant molecular rheology on formation and shear of ultra-thin surface films

Abstract: Abstract. Physics of molecularly thin fluid films, formed between surface features at close range is investigated. It is found that the interplay between discrete lubricant drainage from such contacts and localised contact deflection plays an important role both on the load carrying capacity of these asperity level conjunctions as well as on friction. Small spherical molecules tend to solvate near assumed smooth surfaces of asperities at nano-scale. Their discrete drainage at steadily decreasing gaps adds to t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
25
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 16 publications
(25 citation statements)
references
References 21 publications
0
25
0
Order By: Relevance
“…They include the works reported by Matsuoka and Kato [10], Al-Samieh and Rahnejat [11,12,13] and Chong et al [14] for the study of lightly loaded conjunctions with diminutively thin films, entrained through by hydrodynamic viscous action. To describe solvation, Chong et al [15,16] also adopted the use of Ornstein-Zernike (OZ) equation as expounded by Mitchel et al [17], Henderson and Lozada-Cassou [18] and Attard and Parker [19].…”
Section: Introductionmentioning
confidence: 99%
“…They include the works reported by Matsuoka and Kato [10], Al-Samieh and Rahnejat [11,12,13] and Chong et al [14] for the study of lightly loaded conjunctions with diminutively thin films, entrained through by hydrodynamic viscous action. To describe solvation, Chong et al [15,16] also adopted the use of Ornstein-Zernike (OZ) equation as expounded by Mitchel et al [17], Henderson and Lozada-Cassou [18] and Attard and Parker [19].…”
Section: Introductionmentioning
confidence: 99%
“…In a recent paper, Chong et al [27] showed that near surface effects dominate in gaps of the order of several molecular diameters. They also showed that spherical molecules tend to solvate near assumed smooth surfaces of asperities at nano-scale.…”
Section: Introductionmentioning
confidence: 99%
“…In an evolutionary process to extend the work of Chong et al [27], it is necessary to develop a realistic physio-chemical hydrodynamic model, where intermolecular and surface interactions account for a mix of lubricant molecular species. The current contribution supplements the solution of OZ equation with an attractive narrow well potential to describe the characteristics of a simplified real physical fluid system through PY approximation.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations